Investigating the role of ASPP2 in post-implantation mouse embryos - Sandham, E (2021)
My research focuses on the role of ASPP2 (Apoptosis-stimulating of p53 protein 2, encoded by the TP53BP2 gene) during early post-implantation development. ASPP2 has multiple important biological functions, including roles in the control of cell polarity, tight junction formation, cell proliferation, differentiation and apoptosis.